Desarrollo del área cognitiva a través de herramientas tecnológicas en niños de 24 a 36 meses - Anasi Anchapaxi, Mirian Elizabeth (2017)
This research is about a Mobile Application creating for Children's Cognitive development in 24 to 36 months from Good Living Childcare Centers, (CIBV) at Eloy Alfaro Parish, Latacunga City, and Cotopaxi Province in order to increase and strengthen the children intellectual abilities. The technological, which involve software applications and the pedagogical field were used to do this research that help to know the posed problem and the necessary requirements to the application creating. The implementation was specifically for mobile devices using the Android operating system, the Scrum methodology that allows generating fully functional Product deliverables, through the management model of incremental and interactive Development. In the pedagogical Field was used as the strategies and Piaget and Vygotsky theories who helped Understanding the teaching learning process in the Child Cognitive area development at the pre-Math, using notions, Games….